Efficacy of Follys Catheter Intrauterine Balloon Temponade for the Control of Postpartum Hemorrhage - Faiza Dawood, Razia Bibi, Sidra Pervaiz, Salma, Sadia Hanif, Nighat Afridi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This research aims to determine how well balloon temponade works as a treatment for postpartum bleeding. Study Design: Retrospective Study Place and Duration: Gynaecology and Obstetrics Department, Combined Military Hospital, Peshawar for the duration from February 2021 to January 2022. Methods: Total 118 women had age 18-40 years were presented in this study. Patients who were diagnosed with, or who were admitted to the hospital for treatment of primary postpartum haemorrhage caused by uterine atony were included. Gestational age and parity among all females were recorded. Folly catheter intrauterine ballon tamponade was used and its effectiveness among all cases was assessed. SPSS 23.0 was used to analyze all data. Results: Among 118 cases, 40 (33.9%) cases had age 18-25 years, 55 (46.6%) females had age 26-30 years and 23 (19.8%) cases had age >30years. 75 (63.6%) had BMI <25kg/m2 and 43 (36.4%) had BMI >25kg/m2. Mean gestational age of the females was 36.55±6.72 and mean parity was 3.11±6.9. Mean blood loss was 1208.5±227.9 ml. Mean pulse rate was 106.8±4.97 bpm. Mean systolic and diastolic blood pressure was 88.41±12.7 mmHg and 56.14±8.4 mmHg. Efficacy of balloon tamponade was found in 108 (91.5%) cases. Complications were found in 3 (3.5%) cases. Conclusion: We conclude that follys intrauterine catheter balloon tamponade controls postpartum bleeding. There should be a low threshold for using balloon tamponade as it is effective, easy to use, easily available, has a low complication rate, and is an economical modality to control non-traumatic postpartum haemorrhage, especially in resource-limited settings, and sustain reproductive potential. Keywords: Balloon Temponade, PostPartum Haemorrhage, Efficacy, Complications